The Oxford Movement in context: Anglican high churchmanship, 1760-1857 - Nockles, Peter Benedict ca. 20./21. Jh. (Cambridge University Press, 1994)
This book offers a radical reassessment of the significance of the Oxford Movement and of its leaders, Newman, Keble, and Pusey, by setting them in the context of the Anglican High Church tradition of the preceding 70 years. No other study offers such a comprehensive treatment of the historical and theological context in which the Tractarians operated.